High‐Mobility Air‐Stable Naphthalene Diimide‐Based Copolymer Containing Extended π‐Conjugation for n‐Channel Organic Field Effect Transistors. (17th June 2013) - Kim, Ran; Amegadze, Paul S. K.; Kang, Il; Yun, Hui‐Jun; Noh, Yong‐Young; Kwon, Soon‐Ki; Kim, Yun‐Hi
Abstract A high‐performance naphthalene diimide (NDI)‐based conjugated polymer for use as the active layer of n‐channel organic field‐effect transistors (OFETs) is reported. The solution‐processable n‐channel polymer is systematically designed and synthesized with an alternating structure of long alkyl substituted‐NDI and thienylene–vinylene–thienylene units (PNDI‐TVT). The material has a well‐controlled molecular structure with an extended π‐conjugated backbone, with no increase in the LUMO level, achieving a high mobility and highly ambient stable n‐type OFET. The top‐gate, bottom‐contact device shows remarkably high electron charge‐carrier mobility of up to 1.8 cm2 V−1 s−1 (Ion/Ioff = 106) with the commonly used polymer dielectric, poly(methyl methacrylate) (PMMA). Moreover, PNDI‐TVT OFETs exhibit excellent air and operation stability. Such high device performance is attributed to improved π–π intermolecular interactions owing to the extended π‐conjugation, apart from the improved crystallinity and highly interdigitated lamellar structure caused by the extended π–π backbone and long alkyl groups.